AB0464 Biologic therapy in aortitis: a multicenter study of 30 patients. (23rd January 2014) - Loricera, J.; Blanco, R.; Castañeda, S.; Umbría, A.; Melchor, S.; Rubio, E.; Calvo-Alen, J.; Aurrecoechea, E.; Rúa-Figueroa, I.; Ortego, N.; Minguez, M.; Herrero-Beaumont, G.; et al.
Abstract : Background: Aortitis is the inflammation of the aortic wall, regardless of the underlying condition. It can occur alone or associated with other causes. Aortitis is often refractory to standard immunosuppressive therapy. Objectives: To assess the efficacy and side-effects of biological therapy in patients with inflammatory aortitis. Methods: Multicenter study of 30 patients diagnosed of inflammatory aortitis due to different underlying conditions. The diagnosis of aortitis was based on imaging (CT angiography, MR angiography, PET or echocardiogram). Results: We studied 30 patients (27women/3men); mean age±SD, 47.07±18.62 years. The underlying etiologies were: Takayasu arteritis (TKY) (16 cases), giant cell arteritis (GCA) (7), relapsing polychondritis (2), sarcoidosis (1), ulcerative colitis (1), Sjögren's syndrome (1), Behcet's syndrome (1) and idiopathic aortitis (1) (Table ). In 3 of 30 patients, biological therapy had to be discontinued: 1 GCA with tocilizumab (TCZ) because of neutropenia, 1 GCA with infliximab (IFX) for infusional reactions and 1 TKY with IFX for recurrent pneumonia. Of the remaining 27 patients undergoing biologic therapy, 13 were receiving TCZ (6 TKY, 5 GCA, 1 relapsing polychondritis and 1 idiopathic aortitis), 11 IFX (7 TKY, 2 GCA, 1 Behcet's syndrome, and 1 relapsing polychondritis), 2 were receiving etanercept (2 TKY), 2 rituximab (1 TKY and 1 Sjögren's syndrome) and 2 adalimumab therapy (1 ulcerative colitis and 1 sarcoidosis). Switching from a biologic therapy to another occurred in 8 cases. It was due to inefficacy in 7 cases and allergic reaction in 1 case. After a median [interquartile 25-75] follow-up of 16 [11-24] months most patients experienced clinical improvement and a reduction of ESR levels (from 42.6±29.4 mm/1 st h to 14.8±14.6 mm/1 st h). This fact made possible a reduction in the dose of corticosteroids (prednisone: 25.8±20.5 mg/day to 4.6±3.9 mg/day). Conclusions: Our results indicate that biological therapy seems to be an effective and safe therapeutic option in inflammatory aortitis refractory to conventional immunosuppressive therapy. Disclosure of Interest: None Declared